Nutritional knowledge, eating habits, factors affecting muscle damage, and antioxidant enzyme levels of Korean wrestlers - Lee, Y.-S.; Lee, D.-R.; Lee, H.-R.; Sung, J.-Y. (Physical Activity and Nutrition, 2024)
[Purpose] The aim in this study was to investigate the diet and nutritional knowledge of elite Korean wrestlers and verify the differences in their exercise performance, muscle damage indicators, and antioxidant enzyme levels according to wrestler level. [Methods] A 7-day dietary and nutrition knowledge survey was administered to 30 adult male elite wrestlers (national team: n=11; professional team: n=19). The Wingate test was conducted for 60 seconds to analyze muscle damage indicators and antioxidant levels. Blood and blood lactate concentration analyses were performed four times; the statistical significance level of all data was p<0.05. [Results] Significant differences were found in general nutrition knowledge questionnaire (GNKQ) scores (p=0.043), diet (p=0.001), anaerobic performance (p=0.001), muscle damage indicators (p=0.026), antioxidant levels, and blood lactic acid concentrations (30 min after exercise, p=0.007; 90 min after exercise, p=0.038) between the national and the professional groups. [Conclusion] To the findings confirm the relationship between the differences in diet, nutrition, and motor function for wrestlers of different expertise levels. In a follow-up, a comprehensive study on nutrition knowledge, athlete training, and weight loss is needed that considers a wider scope of subjects and analyzes additional variables.